Flaxseed additive application in dairy products production - Ivanov, Sergey; Rashevska, Tamara; Makhonina, Marina (My University, 2011)
New butter with flaxseed additive and flaxseed additive technology were developed by us. The suspension microstructure of flaxseed additive was studied.
Keywords: dairy products; flax seed; microstructure; молочні продукти; насіння льону; мікроструктура; кафедра технології молока і молочних продуктів; кафедра експертизи харчових продуктів